(untitled) (Bangladesh Journal of Botany, 2024)
An experiment was conducted during the cropping season of 2018 and 2019 to determine how plant ages affect flowering, fruit quality and incidence of sunburn and fruit cracking in litchi cv. Rose Scented. In a lot consisting of litchi plants aged between 1 and 30 years, 25-30- years-older plants initiated panicle emergence earlier with larger-sized panicles (42.35 cm length and 28.65 cm spread) and thicker peduncle (>6 mm). Fruit retention per panicle was also more in number (15.68) in 25-30- years older plants as compared to 1-5 year younger plants (4.76). An important observation involved fruits being borne closer to leaf in 25-30- years-older plants, which ultimately resulted in lesser incidence of sun burn and fruit cracking. Older plants (25-30-years) produced bigger fruit than 1-5 year-younger ones and highest fruit weight (22.58g) was recorded in 15–20-year-old plant. The time taken for fruit borne in older trees (25-30-years) to attain optimum fruit maturity was extended or delayed by 5 days as compared to younger plants (1-5-year). Total soluble solids was also higher in fruits borne on 25-30 years older litchi plants, while titratable acidity and ascorbic acid contents was more in fruits borne on 1-5 year younger plants. Total phenolics and antioxidant activity of pulp were the highest in young plants and least in older plants. we conclude that heavy bunches and proximity of fruit to leaf are important traits in litchi for consideration in breeding programmes to identify clones or variants tolerant to sun burn and fruit cracking. Bangladesh J. Bot. 53(2): 279-285, 2024 (June)